Residual stress characterization of single and triple-pass autogenously welded stainless steel pipes. (August 2016) - Haigh, R.D.; Hutchings, M.T.; Fitzpatrick, M.E.; James, J.A.; Okido, S.; Mizuno, R.; Ogawa, K.; Hughes, D.J.
Abstract: Using neutron diffraction the components of the residual stress field have been determined in the region near a mid-length groove in two identical austenitic stainless pipes in which weld beads had been laid down. One pipe sample had a single pass, and the second a triple pass, autogenous weld deposited around the groove circumference. The results show the effect on the stress field of the additional weld deposited and are compared to the results of Finite Element Modelling. The hoop stress component is found to be generally tensile, and greater in the triple pass weldment than in the single pass weldment. The hoop stresses reach peak values of around 400 MPa in tension. X-ray measurements of the residual stress components on the near inner surface of the pipe weldments are also presented, and show tensile stresses in both pipes, with a higher magnitude in the three-pass weldment. Highlights: Neutron diffraction residual stress measurements made in 1-pass and 3-pass pipe weldments of 304 austenitic stainless steel. Variation of residual stress with azimuthal angle α determined. At the centre of the weld groove the axial residual stress undergoes a transition from tension to compression through α = 0. This effect is larger in the single-pass than in the triple-pass weldment. Hoop stress is generally tensile, and greater in the 3-pass weldment, reaching peak values of around 400 MPa.